2007
DOI: 10.1016/j.juro.2006.08.145
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Dismembered Pyeloplasty in Children Younger Than 2 Years

Abstract: This study suggests that laparoscopic pyeloplasty can now be performed in young children with good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 19 publications
3
33
0
1
Order By: Relevance
“…Although adhesions may occur with urological laparoscopic procedures, the incidence appears lower than would be expected with open exploration 14 . Laparoscopic dismembered pyeloplasty is an acceptable option for UPJO in infants and younger children [13][14][15] . A recent report has demonstrated that laparoscopic dismembered pyeloplasty is technically possible in infants younger than 6 months 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although adhesions may occur with urological laparoscopic procedures, the incidence appears lower than would be expected with open exploration 14 . Laparoscopic dismembered pyeloplasty is an acceptable option for UPJO in infants and younger children [13][14][15] . A recent report has demonstrated that laparoscopic dismembered pyeloplasty is technically possible in infants younger than 6 months 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in performing LP that we found at the beginning of the series was in performing the anastomosis, but we completed with patience with relatively longer operating time but other author converted to open operation for difficulty in anastomosis 17 . The use of 3-mm trocars are recommended to perform this procedure 15,18 , but we used one 10 mm for camera port and two 5 mm port as we are lacking 5 mm telescope and 3 mm port and grasper as well. Double J catheter placement during LP is another recommendation, since it prevents urinary leakage and obviates the need for a perianastomotic drain 13,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The initial access was made with a Veress needle, except in the few cases with previous abdominal surgery or marked obesity, in which a Hasson (open) technique was used. In 4 cases, Details of the surgical technique have been previously described, but some technical points should be stressed (9)(10)(11)(15)(16)(17). In the UPN, after exposing the hilum, the diseased ureter is divided distally, almost always at the level of the iliac vessels, preserving the normal ureter.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Reconstructive and ablative renal procedures have been reported with increasing frequency, with safety and success (9)(10)(11)(12)17). The presence of malignant pathology was one of the few limitations yet to be transposed in pediatric renal laparoscopy.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation